2021
DOI: 10.3390/membranes11100772
|View full text |Cite
|
Sign up to set email alerts
|

The Cytoplasmic Tail of Influenza A Virus Hemagglutinin and Membrane Lipid Composition Change the Mode of M1 Protein Association with the Lipid Bilayer

Abstract: Influenza A virus envelope contains lipid molecules of the host cell and three integral viral proteins: major hemagglutinin, neuraminidase, and minor M2 protein. Membrane-associated M1 matrix protein is thought to interact with the lipid bilayer and cytoplasmic domains of integral viral proteins to form infectious virus progeny. We used small-angle X-ray scattering (SAXS) and complementary techniques to analyze the interactions of different components of the viral envelope with M1 matrix protein. Small unilame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
(68 reference statements)
1
8
0
Order By: Relevance
“…We observed that, in the case of bPS-containing raft GUVs, the addition of the M1 protein led to the division of the vesicle into a raft and a non-raft one ( Figure 8 ). This is aligned with the observed widening of the electron density profile of the membrane with M1, as detected by SAXS in [ 38 ], due to the change of the initial spherical shape of the vesicle to a more prolate dumbbell one. BSA and PLL did not exhibit such behavior ( Figure 9 and Figure 10 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We observed that, in the case of bPS-containing raft GUVs, the addition of the M1 protein led to the division of the vesicle into a raft and a non-raft one ( Figure 8 ). This is aligned with the observed widening of the electron density profile of the membrane with M1, as detected by SAXS in [ 38 ], due to the change of the initial spherical shape of the vesicle to a more prolate dumbbell one. BSA and PLL did not exhibit such behavior ( Figure 9 and Figure 10 ).…”
Section: Discussionsupporting
confidence: 88%
“…M1 electrostatically interacts with anionic lipids of the inner leaflet of the plasma/viral membrane [ 34 ]. Anionic phosphatidylserine (PS) enhances the M1 oligomerization on the membrane [ 35 , 36 ], probably leading to the formation of membrane invaginations [ 37 , 38 ]. The presence of phosphatidylinositol 4,5-bisphosphate (PIP2) clusters M1 protein, possibly due to the high surface charge density [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the pioneering work of Gregoriades and Oxford [ 54 , 55 ], PS has been identified as the main target for the membrane association of IAV M1 [ 16 , 56 , 57 ]. Recently, the effect of lipid composition on the initiation of M1 self-assembly has been studied using SUVs (small unilamellar vesicles) and proteoliposomes, showing the role of lipid ordering in the association of M1 to PS in these liposomes [ 58 ]. Liposomes were also used to monitor the interactions of virus proteins such as HA [ 55 ] and NA [ 59 ] with lipids and lipid redistribution; however, this was essentially considered during membrane fusion [ 60 ], which is the entry step (early phase of replication) of the virus, not the assembly step.…”
Section: Artificial Lipid Membranes As Tools For Viral Assembly Researchmentioning
confidence: 99%
“…For instance, the CT of human immunodeficiency virus type 1 (HIV-1) envelope protein gp41 interacts with the Gag protein, which contribute to the enrichment of gp41 at the viral packaging site for subsequent efficient packaging into viral particles ( Muranyi et al, 2013 ; Postler and Desrosiers, 2013 ; Roy et al, 2013 ; Tedbury and Freed, 2015 ). In addition, the interactions between the CT of the HA protein or NA protein of influenza A virus and the M1 protein facilitate the maintenance of the correct subcellular localization and packaging of viral particles ( Barman et al, 2004 ; Jin et al, 1997 ; Kordyukova et al, 2021 ). Moreover, the CT of respiratory syncytial virus fusion protein mediates virion assembly through incorporation of internal virion proteins into virus filaments at the cell surface ( Baviskar et al, 2013 ; Shaikh et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%